2021
DOI: 10.3390/app11178196
|View full text |Cite
|
Sign up to set email alerts
|

A Recent Study on Remediation of Direct Blue 15 Dye Using Halloysite Nanotubes

Abstract: A set of lab-scale experiments were designed and conducted to remedy Direct Blue 15 (DB15) dye using nontoxic halloysite nanotubes (HNT) with the view to be utilized in a textile industrial effluent (TIE). The DB15 adsorbed-HNT “sludge” was used as a reinforcing agent and plastic waste to fabricate the composite. To advance the knowledge and further understand the chemical phenomena associated with DB15 adsorption on HNT, different factors like pH value, adsorbate initial concentration, adsorbent dosage, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Our research school has demonstrated pioneering efforts to use NIS as filler material for the fabrication of composites [49][50][51][52] and as an adsorbent for the bioremediation of toxic dyes [53][54][55][56][57][58][59][60][61][62][63][64]. Recently, our research school has demonstrated circular economy at the laboratory scale using NIS [65].…”
Section: Introductionmentioning
confidence: 99%
“…Our research school has demonstrated pioneering efforts to use NIS as filler material for the fabrication of composites [49][50][51][52] and as an adsorbent for the bioremediation of toxic dyes [53][54][55][56][57][58][59][60][61][62][63][64]. Recently, our research school has demonstrated circular economy at the laboratory scale using NIS [65].…”
Section: Introductionmentioning
confidence: 99%
“…The major barriers to the SME shift from a linear economy to CE include the following reasons: administrative burden, company’s environmental culture, innovation policies, technological know-how and privation of capital, effective legislation, government inadequate financial support and lack of information and technical back-up [ 53 ]. All these barriers are of no concern if the raw material is replaced with dye-adsorbed NIS or nanomaterials [ 54 , 55 , 56 ], which requires only optimising process parameters before production using the same machinery and know-how.…”
Section: Resultsmentioning
confidence: 99%
“…It was noticed (Figure 4), that the percent of MV adsorption grew significantly from 91-99.9%, with the increase of adsorbent dosage from 0.025 to 0.2 g. Thereafter, by increasing the adsorbent dosage up to 0.4 g, an insignificant increase in the removal efficiency was observed [63].…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 91%
“…It was noticed (Figure 4), that the percent of MV adsorption grew significantly from 91-99.9%, with the increase of adsorbent dosage from 0.025 to 0.2 g. Thereafter, by increasing the adsorbent dosage up to 0.4 g, an insignificant increase in the removal efficiency was observed [63]. It was also found that the enhancement of adsorbent dosage, resulted in a decrease in the amount of adsorbed dye per unit mass of adsorbent, from 91.3 to 6.3 mg/g.…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 92%